Problems of conception : issues of law, biotechnology, individuals and kinship - Melhuus, Marit (Berghahn Books, 2012)
The Biotechnology Act in Norway, one of the most restrictive in Europe, forbids egg donation and surrogacy and has rescinded the anonymity clause with respect to donor insemination. Thus, it limits people's choice as to how they can procreate within the boundaries of the nation state. The author pursues this significant datum ethnographically and addresses the issues surrounding contemporary biopolitics in Norway. This involves investigating such fundamental questions as the relation between individual and society, meanings of kinship and relatedness, the moral status of the embryo and the role of science, religion and ethics in state policies. Even though the book takes reproductive technologies as its focus, it reveals much about vital processes that are central to contemporary Norwegian society.